Comparison of self-esteem and quality of life between residents of old people's home and the elders living at home - Pluzarić, Jadranka (Obzornik zdravstvene nege, 2016)
Introduction: Research on self-esteem and quality of life has been so far predominantly focused on younger age groups. The aim of this cross-sectional study was to examine the differences regarding self-esteem and quality of life between the residents of old people's home and the elders living at home. Methods: A questionnaire used in the survey inquired about socio-demographic data and the respondents' activities. It included the respondents' self-esteem assessment, based on the Rosenberg Self-esteem Scale (RSES), the assessment of quality of life, based on the Satisfaction With Life Scale (SWLS) and the assessment of their functional abilities. The purposive sample included 204 respondents. The research was conducted from November 2012 to March 2013. Results: The respondents in both groups expressed equal satisfaction with life (p = 0.846). The respondents who live in their own home demonstrate higher self-esteem than those who live in old people's home (difference in mean scores of the RSES was 3.4; 95 % CI for the difference from 1.0 to 5.8; t-test for independent samples, p = 0.005). Results of the study suggest that the respondents with higher self-esteem are more satisfied with their life (p = 0.537, p < 0.001). Discussion and conclusion: Self-esteem has to be recognised as a factor associated with the quality of life and should therefore be included in the care of the elderly. Timely and adequate interventions may prevent the decline in quality of life, which requires adequate training of health personnel and family members, and the public awareness.
Keywords: bivanje; elderly; fizična aktivnost; housing; physical activity; samospoštovanje; stanovanje; starejši ljudje